2021
DOI: 10.4103/jfmpc.jfmpc_1259_20
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception of medications safe storage in the State of Qatar

Abstract: Purpose: The purpose of this study is to identify parental perception of household medication storage. Methods: A prospective cross-sectional study utilizing a questionnaire was carried out at Hamad Medical Corporation, the solely tertiary pediatric hospital in the State of Qatar at the time of the study. Qatar is a young developing country with limited data on the awareness of medication storage among adults with children at home and on the safety practices regarding m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Most of the mothers stored medication in the fridge and at a level above adults' eyes (at reach). These findings were concordant with Hendaus M et al's study [ 13 ], which found that 57.4% of parents stored medications at home and 90% of the parents kept their prescriptions in easily accessible locations. Ten percent of caregivers keep several prescriptions in one container, and the same proportion of participants do not check the labels for expiration dates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most of the mothers stored medication in the fridge and at a level above adults' eyes (at reach). These findings were concordant with Hendaus M et al's study [ 13 ], which found that 57.4% of parents stored medications at home and 90% of the parents kept their prescriptions in easily accessible locations. Ten percent of caregivers keep several prescriptions in one container, and the same proportion of participants do not check the labels for expiration dates.…”
Section: Discussionsupporting
confidence: 91%
“…Enormous storage of medication can be attributed to several factors, including excessive physician prescription, excessive purchasing, and nonadherence to treatment. In addition, there was a significant relationship between the number of medications stored in households and factors such as insurance coverage, chronic illnesses (such as diabetes mellitus, hypertension, cardiovascular disease, and cancer), siblings not working in health-related jobs, higher economic status, and literacy of the father and parents who have children less than six years old [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%